White Lies - Reade, Charles, 1814-1884 (Salt Lake City, UT : Project Gutenberg, 2006)
"White Lies" by Charles Reade is a novel written during the late 19th century, which explores themes of nobility, loss, and the complexities of social class during a time of political upheaval in France. The story centers on the family of the late Baron de Beaurepaire, particularly his widow and two daughters, Josephine and Rose, as they navigate life after the baron's death against the backdrop of the French Revolution and its societal ramifications. At the start of the novel, we are introduced to the Baron de Beaurepaire and his esteemed family lineage, which is now threatened by the tumultuous political landscape following the Revolution. The baroness and her daughters grapple with financial difficulties and the loss of their social standing while reflecting on their past prosperity. The baroness, supported by close family friend Dr. Aubertin, tries to maintain their dignity despite their declining circumstances. The story unfolds to reveal the sisters' budding interactions with Edouard Riviere, a young official who becomes increasingly intrigued by them, setting the stage for the exploration of class, honor, and romance amidst their struggles. (This is an automatically generated summary.)
Release date is 2006-05-17
Produced by Donald Lainson; David Widger
Keywords: France -- History -- Wars of the Vendée, 1793-1832 -- Fiction; Marriage -- Fiction